The Involvement of the Gampong Government in Aceh in Recruiting Local Workers to Prevent Violent Community Conflicts in the Corporate Environment - Rizki Yunanda; Teuku Kemal Fasya; Richa Meliza; Kurniawati Kurniawati; Dini Rizki (LPPM Universitas Malikussaleh, 2024)
In Indonesia, the presence of foreign workers (TKA) has increased rapidly, reaching 110,833 people in 2022, a jump of 25.6% compared to the previous year. Although the contribution of foreign workers in development and investment is undeniable, conflicts often arise between foreign workers and local workers. Dissatisfaction with transparency and fairness in the process of accepting local workers, involving the Gampong government, has led to social tensions. Social jealousy, in which local communities feel marginalized, is often a trigger for conflict. This study aims to understand the form of conflict resolution carried out by the Gampong government on the policy of accepting local workers in the Company's environmental villages and the steps taken by the Gampong government to align the policy of accepting local workers with the needs and aspirations of the people of the company's environmental villages. Perspective of conflict resolution theory. Data collection is carried out through Live in, observation, in-depth interviews and the use of documents. The data analysis process is carried out interactively through stages; data collection, data verification, data patterns, data coding, data thematic networks, meaning and drawing conclusions. The conflict related to the policy of accepting local workers in Dewantara District is caused by the community's dissatisfaction with the company's policies. The solution involves an inclusive approach and dialogue between the company, government, and community. Steps such as mapping labor needs, training, and collaboration between sectors are crucial to improving the quality of the local workforce.